Role of Yersinia pseudotuberculosis outer proteins (Yops) in murine humoral immune response - Maia, J. M. L. [UNESP]; Monnazzi, L. G. S. [UNESP]; Medeiros, B. M. M. (Springer, 2009)
The infection of mice with the wild-type (WT) strain of Y. pseudotuberculosis did not induce polyclonal activation of B lymphocytes. Suppression in the production of certain isotypes of Ig was observed, provoked mainly by YopH, YopJ and YpkA. The WT strain induced a progressive increase in the serum-specific IgG, which peaked after 4 weeks after infection, IgM being produced only after 1 week. Autoantibodies against phosphorylcholine, myelin, thyroglobulin and cardiolipin could be detected in the serum of mice infected with the WT strain. The infection of mice provoked suppression in the production of immunoglobulins by splenic B cells and that YopH, YopJ and YpkA must be involved here.